Analisis Kebutuhan Debit Air Di Gedung C RSUD Kota Bukittinggi - Mela Melarizki Rizki; Muchlisi Nalahuddin; Riza Muharni (Politeknik Negeri Padang, 2021)
In the Bukittinggi City Hospital building which has 6 floors, there is a water pump and a reservoir used to supply clean water for daily needs. Based on the reality in the field where there is no secondary data to determine the type of pump and reservoir. The purpose of this analysis is to obtain clean water discharge requirements, obtain the type of pump and ensure that the reservoir used for building C RSUD Kota Bukittinggi is in accordance with the type of pipe and reservoir installed in building C, floor 6. By using field studies and interviews and applying the formulas related to pump calculations. In determining the type of pump to be used in the building, it includes the required water discharge, determining the capacity of the components to be used such as pipe diameter, water tank capacity on the ground floor and roof of the building and the total head on the pipe. Based on the calculation results, the required water discharge is 0.08333 m 3 /min, the upper reservoir has a capacity of 150,000 liters, the bottom reservoir is 5,000 liters and the Hot that occurs is 18.429 m. Then the required pump specifications are 40 x 32B2 -51.5 Grundfos CM 10-3. The pump specifications are not much different from those that have been applied in the field.